2020
DOI: 10.1007/s13204-020-01364-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured AlNiCoFeCrTi high-entropy coating performed by cold spray

Abstract: In this work, solid-state mechanical alloying (MA) and cold spraying (CS) processes were applied to fabricate powder AlNiCoFeCrTi high-entropy alloy (HEA) and then to produce HE coatings on steel substrate. Shot-time MA for 3 h has been employed to synthesize nanostructured equiatomic AlNiCoFeCrTi HEA of metastable supersaturated substitutional solid solution with bcc crystal structure. Although alloying is not complete at this shot milling time, it goes to completion during thermal annealing to achieve the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Hushchyk et al cold sprayed AlNiCoFeCrTi HEA milled powder on the steel substrate. Their results confirmed that HEA coatings were produced with low porosity as a low-temperature process and there was no phase composition change in HEA coating without any phase transformation [76]. The AlNiCoFeCrTi HEA coatings were highly dense and vary from 430-470 µm in thickness.…”
Section: Methods Of Fabrication Of Hea Coatingsmentioning
confidence: 60%
See 1 more Smart Citation
“…Hushchyk et al cold sprayed AlNiCoFeCrTi HEA milled powder on the steel substrate. Their results confirmed that HEA coatings were produced with low porosity as a low-temperature process and there was no phase composition change in HEA coating without any phase transformation [76]. The AlNiCoFeCrTi HEA coatings were highly dense and vary from 430-470 µm in thickness.…”
Section: Methods Of Fabrication Of Hea Coatingsmentioning
confidence: 60%
“…By using various sources of energy, such as thermal, electrical, or mechanical energy to achieve fine-grained [71,[88][89][90]. Various authors have used mechanically alloyed HEA powder for plasma spraying on a harder substrate [76,91]. Tian et al ball-milled AlCoCrFeNiSi HEA powder for 10 h to obtain BCC and FCC dual-phase HEA alloy which was further plasma sprayed on 316 stainless steel substrates.…”
Section: Methods Of Fabrication Of Hea Coatingsmentioning
confidence: 99%
“…Web of Science 2019 Deposition of FeCoNiCrMn high entropy alloy (HEA) coating via cold spraying [200] First report on cold-sprayed AlCoCrFeNi high-entropy alloy and its isothermal oxidation [269] 2020 Cold Gas Spraying of a High-Entropy CrFeNiMn Equiatomic Alloy [207] Nanostructured AlNiCoFeCrTi high-entropy coating performed by cold spray [270] Table 9. Cont.…”
Section: Database Year Title Of the Published Paper Refsmentioning
confidence: 99%
“…Currently, most authors have developed HECs by using different coating methods such as magnetron sputtering [ 95 , 96 , 97 ], laser cladding [ 98 , 99 ], induction cladding [ 100 ], plasma spraying [ 54 , 69 , 70 , 97 ], electrodeposition [ 101 ], high velocity oxy-fuel (HVOF) [ 41 , 50 , 51 , 54 , 55 , 56 , 59 , 61 , 65 ], cold spraying [ 102 , 103 , 104 , 105 ] and many others. Moreover, numerous methods are available to prepare the powder before cladding/spraying to get into a uniform size and shape, including atomization, mechanical alloying, and ball milling.…”
Section: High-entropy Alloys (Heas) and Coatings (Hecs)mentioning
confidence: 99%